Development of Coconut Milk-Based Spicy Ice Cream as a Nondairy Alternative with Desired Physicochemical and Sensory Attributes - K. D. S. S. Perera; O. D. A. N. Perera (International Journal of Food Science)
Spices have been a major influence on Sri Lankan cuisine since times immemorial. Spices are identified as one of the most distinctive ingredients for their indigenous flavor, aroma, and medicinal properties. In this study, coconut milk-based spicy ice cream was developed in compliance with the Sri Lankan standards to introduce a new perception of flavor using spices to the ice cream industry. Although coconut ice cream is commercially available in the local market, spicy flavored coconut ice cream is not yet available. Cinnamon (Cinnamomum verum), ginger (Zingiber officinale), and white pepper (Piper nigrum) are the spices used in the preparation of the ice cream as they are freely available and used as complementary spices in Sri Lanka. Physicochemical characteristics and sensory attributes of coconut milk-based spicy ice cream were compared with the existing normal coconut ice cream. In preparation of the ice cream, the same ice cream manufacturing process was followed with some modifications. Three different formulas (0.010%, 0.018%, and 0.025%) were developed by changing the percentage of spices added. The 0.018% spice-added sample was selected as the most acceptable ice cream with desired sensory attributes. pH (6.33±0.01), titratable acidity (0.33±0.05%), moisture (61.86±0.33%), ash (0.41±0.25%), total solids (38.02±0.14%), overrun (66.76±1.44%), protein (4.18±0.16%), and fat content (11.66±0.60%) were evaluated as physicochemical properties. Total phenolic content of the ice cream was expressed as 0.093±0.002 mg gallic acid equivalents (GAE) per gram of sample in dry weight (mg/g). DPPH radical scavenging activity was 60.39±0.02 mg ascorbic acid equivalents per gram of sample in dry weight (mg/g), and total antioxidant capacity was expressed as 0.36±0.04 mmol ascorbic acid equivalent (AAE)/g of dry weight. Physicochemical properties of spicy coconut ice cream were more or less similar to that of normal coconut ice cream and in compliance with the Sri Lankan standards. Coconut milk-based spicy ice cream could be introduced to the market as a potential marketable nondairy product with spicy flavor, aroma, and smooth texture.